Treatment of the corporate rule from the economic perspective Hard Law vs Soft Law - Vigil Oliveros, Enrique (2019)
The main purpose of this article is to analyze the impact of the corporate rules described in the General Corporation Law in force in our company for the constitution, operation and orderly exit of the market. The economic reality in our country seems not to be consistent with the legal reality, even being in several provisions a divorce between these two sciences that unleashes damage to societies in the delay in procedures that result in economic losses. In this article, the analysis will seek the solution through overcoming the deficiencies of corporate norms by building permissive standards for the best business development.